1998
DOI: 10.1099/00222615-47-9-821
|View full text |Cite
|
Sign up to set email alerts
|

Clinical evaluation of the Mycobacteria Growth Indicator Tube (MGIT) compared with radiometric (Bactec) and solid media for isolation of Mycobacterium species

Abstract: A us tra liaThe aim of this study was to evaluate the clinical use of a new culture system for the isolation of mycobacteria. Routine clinical specimens were cultured in the Mycobacteria Growth Indicator Tube, the radiometric Bactec 460 TB system and on Lowenstein Jensen (LJ) medium to compare recovery rates and times for detection of mycobacteria and contamination rates. MGIT was tested for its ability to support the growth of a wide range of mycobacterial species. Acid-fast bacilli (AFB) were detected on dir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
29
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 6 publications
4
29
0
1
Order By: Relevance
“…[20] Chew et al had shown the mean detection time to be 27 days with LJ medium. [18] Our findings were in agreement to other studies.…”
Section: Totalsupporting
confidence: 83%
See 1 more Smart Citation
“…[20] Chew et al had shown the mean detection time to be 27 days with LJ medium. [18] Our findings were in agreement to other studies.…”
Section: Totalsupporting
confidence: 83%
“…However, in literature sensitivity of LJ medium had been reported to be 59.7%, 76.9% and 87%. [17,18,19] The mean detection time for isolation of mycobacteria on LJ media was 32.88 ± 12.07 days. It was then separately computed for AFB smear negative and AFB smear positive specimens.…”
Section: Totalmentioning
confidence: 99%
“…One of them could be the use of a solid culture medium, which has a lower sensitivity than liquid media such as MGIT (20). Second, quality control of the SMF readings was not performed mainly because the bacillus staining of the SMF fades away after 24 h. As the two staining methods use the same stain, it might be possible that the remaining hypochlorite and/or Triton X-100 in the membrane fades the stain.…”
Section: Discussionmentioning
confidence: 99%
“…In most of the research studies published two culture media were used to assess the performance of the Xpert MTB/RIF® test: the Löwenstein-Jensen solid medium and the BACTEC MGIT automated liquid medium; however, many hospitals only have the Ogawa-Kudoh solid medium. It is known that the use of solid and liquid culture media can increase the sensitivity by 11% or more (16,17). The conventional culture medium requires 10 2 mycobacteria to detect positivity and the PCR requires only 10 or more mycobacteria.…”
Section: Discussionmentioning
confidence: 99%